Family Development Session Sebagai Program Anti-Kemiskinan di Desa Pungut Hilir? Kajian atas Efektivitas dan Kemandirian - Annisa, Yulia; Kamal, Tamrin; Alkhendra, Alkhendra (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2020)
This article tries doing to the correlation of program effectiveness through self-reliance for people who are to be a benefits program of cash conditional transfer. The research was used as a quantitative method by correlation of linear regression analysis. Data was collected by collecting of questionnaire process to respondents. The researcher takes respondents who are getting 11 persons with a simple random sampling technic. This study finds that empowerment has been implemented by the schedule and routine activities that it can increase 9,1% for the effectiveness of family development session action. Meanwhile, the family development session was implemented effectively that it was able to rise of advantages for their program in Pungut Hilir Village. The program as well as effectively has been increased for beneficiaries who are occurring of 70,1% self-reliance that is explained by other factors of 29,9% impact. In contrast, this program can be a rising of 70,1% self-reliance for beneficiaries but it is not maximalising for the terminate of anti-poverty. It becomes of dependency people who assist with programs from the government. Society cannot self-standing and less creativity for well-being in their life. This is an impact on people who are powerless and trapped in a culture of poverty that is the effect of hereditary. This condition will become of people who are higher than hanger to the assistance of the program. Artikel ini mencoba untuk melakukan uji korelasi efektivitas program terhadap kemandirian keluarga penerima manfaat program keluarga harapan. Pengujian korelasi ini menggunakan metode kuantitatif dengan uji regresi linier. Data dikumpulkan melalui proses penyebaran angket (kuesioner) kepada para responden. Peneliti membatasi responden yang hanya mengambil 11 orang dengan teknik simple random sampling. Studi ini menemukan bahwa pelaksanaan kegiatan pemberdayaan secara rutin dan terjadwal dapat meningkatkan efektivitas kegiatan family development session sebesar 9,1%. Sementara itu, pelaksanaan kegiatan family development session secara efektif dapat meningkatkan keluarga penerima manfaat program di Desa Pungut Hilir. Adapun efektivitas program telah mengalami peningkatan kemandirian sebesar 70,1% dengan dijelaskan oleh faktor sebesar 29,9%. Walaupun program tersebut dapat meningkatkan kemandirian namun upaya memberantas kemiskinan tidak berjalan maksimal. Hal ini menjadikan masyarakat ketergantungan dengan bantuan yang diberikan oleh pemerintah. Masyarakat menjadi tidak mandiri serta kehilangan kreatifitas dalam memenuhi kehidupan sehari-hari. Dampak yang terjadi menjadikan masyarakat tidak berdaya dan terjebak dalam budaya kemiskinan yang turun temurun. Kondisi ini menjadikan tingkat ketergantungan masyarakat terhadap bantuan yang semakin tinggi.